The legacy effect of squatter settlements on urban redevelopment - Ignacio A. Navarro; Geoffrey K. Turnbull (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
The paper presents a theoretical model that seeks to answer the question of why former squatter settlements tend to upgrade/redevelop at a slower pace than otherwise similar settlements originating in the formal sector. We argue that squatter settlers' initial strategy to access urban land creates a 'legacy effect' that curtails settlement upgrading possibilities even after the settlements are granted property titles. We test our model using the case of Cochabamba, Bolivia and obtain results consistent with our theoretical model prediction. Our results suggest that the commonly used 'benign neglect while keeping the threat of eviction' policy has profound impacts on how land is developed in the informal sector and this poses costly consequences for local governments after legalization.
Keywords: R14; R52; O43; 330; squatters; informal settlements; urban development; neighbourhood upgrading; urban redevelopment